Avaliação ambiental estratégica: proposta de integração ao plano diretor estratégico de São Paulo - Machado, Débora Mendonça Monteiro (2018)
The Strategic Environmental Assessment [SEA] is an instrument of environmental planning adopted in more than sixty countries, without systematic and mandatory practice in Brazil. There is theoretical and practical evidence that the SEA has been increasing the incorporation of the environmental variable in urban planning, where it is regularly applied. Given this context emerges the following question: How to integrate the Strategic Environmental Assessment into municipal master plans? Thus, the objective was to propose the integration and use of SEA in the Strategic Master Plan of the city of São Paulo [PDE-SP]. This study is characterized as qualitative-exploratory and the systematic review of the literature was used to analyze the diffusion of technical-scientific knowledge, in order to constitute the theoretical reference of this study and to carry out surveys and analyzes at the national and world level. As a data collection stage, the documentary research was carried out, which consisted in the analysis of manuals, Good Practices Guidelines, the São Paulo Municipal Master Plan [PDE-SP], and 17 other master plans of municipalities around the world. Analyzes were performed on theoretical methodologies; theories related to the master plan; evaluation of good practices included in the 20 municipal master plans; analysis of the structure of the PDE of São Paulo and its relations with the SEA. Regarding the results, it can be considered that the Brazilian production of SEA is immature and is in an early stage of development. Thus, this study reacts to the lack of legal obligation for its application in the country, with the elaboration of a proposal for integration and consequent use of the SEA in the PDE-SP. It is concluded that this study allows to evaluate the application of the SEA in urban planning in a world-wide context, adapting its stages of knowledge and application to Brazil; points out its use in the revision of the instrument with an SEA integration framework to the SPDP. The study reinforces the concern to elucidate forms for application in the country and points promising paths for future research.